Sexual Orientation and the Canadian Labour Movement - Hunt, Gerald (Relations industrielles / Industrial Relations, 1997)
The response of the Canadian labor movement to sexual orientation discrimination has been mixed and uneven. The Canadian Labour Congress, along with several provincial federations and a growing number of unions, have taken a leadership role in promoting equal rights for gays and lesbians, while other labor organizations have done nothing at all. Public sector and Canadian-based unions are much more likely to have been active than have American-based unions, even though there are important exceptions to these trends. These developments are partially explained by regional dynamics, membership demographics, degree of activism, the presence of women's committees, and organizational leadership.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Discrimination; Employment discrimination; Gays & lesbians; Labor Unions; Manycompanies; Polls & surveys; Ratings & rankings; Rights; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical data